1974
DOI: 10.1128/iai.10.4.695-699.1974
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Development and Aging on the Response of Canine Lymphocytes to Phytohemagglutinin

Abstract: The stage of development and age were found to effect the responsiveness of dog T-lymphocytes to phytohemagglutinin. T-lymphocytes from beagles 0 to 4 weeks of age showed significantly less response to phytohemagglutinin ( P < 0.001) than T-lymphocytes from these same dogs at 6 to 12 weeks of age. Peak response to phytohemagglutinin occurred between 6 weeks to 6 months of age, after which there was a significant correlation ( P < 0.02) between increase in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1977
1977
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The distribution of lymphocyte subpopulations in normal adult canine lymphoid tissues is well characterised (Rabanal and others 1995) and such cells have recently been enumerated in the gastrointestinal tract of normal adult dogs (Kolbjornsen and others 1994, Jergens and others 1996, German and others 1999a. Although data are not available for pups of 16 to 20 weeks of age, the numbers of T cells observed in the tissues of these pups were below the level that JOURNAL OF could reasonably be attributed to an agerelated effect (Gerber andBrown 1974, Sellon andothers 1996) (Hart 1979, Hogenesch andFelsburg 1992). These observations correlate with the markedly low serum immunoglobulins in this case.…”
Section: Dog 12mentioning
confidence: 87%
“…The distribution of lymphocyte subpopulations in normal adult canine lymphoid tissues is well characterised (Rabanal and others 1995) and such cells have recently been enumerated in the gastrointestinal tract of normal adult dogs (Kolbjornsen and others 1994, Jergens and others 1996, German and others 1999a. Although data are not available for pups of 16 to 20 weeks of age, the numbers of T cells observed in the tissues of these pups were below the level that JOURNAL OF could reasonably be attributed to an agerelated effect (Gerber andBrown 1974, Sellon andothers 1996) (Hart 1979, Hogenesch andFelsburg 1992). These observations correlate with the markedly low serum immunoglobulins in this case.…”
Section: Dog 12mentioning
confidence: 87%
“…Within each of the four groups of normal, gingivitis, mild to moderate and advanced periodontitis, the variability in PHA stimulation is evident. Several in vitro factors, such as duration of culturing (Douglas, Kamin & Fudcnberg 1969), as well as host parameters, such as aging (Gerber & Brown 1974) and disease state (Notkins, Mergenhagen & Howard 1970, Saiaman 1970, Kauffman et al 1974, may influence the responsiveness of T-lymphocytes to PHA. A marked increase of the peak response of PBL following stimulation with PHA during human experimental gingivitis has recently been associated with a shift of that peak response to lower PHA concentrations (Lang & Smith 1976).…”
Section: Lymphocyte Transformation In Patients With Periodontal Diseasementioning
confidence: 99%
“…This response may miss the peak response, making proper evaluation difficult. b) A significantly depressed response of PBL to mitogen (PHA) has been demonstrated with increasing age in the canine (Gerber & Brown 1974), as well as in humans (Weksler & Hutteroth 1974). Furthermore, Holm-Pedersen, Gaumer & Folke (1975) reported that elderly subjects would lack a response associated with gingival inflammation when their PBL were stimulated with lipopolysacharide from the cell walls of gram-negative organisms.…”
Section: Lymphocyte Transformation In Patients With Periodontal Diseasementioning
confidence: 99%
“…In vitro problems, including antigen dose-response relationships (Kiger, Wright & Creamer 1974, Lang c& Smith 1976) and the addition of serum to culture (Ivanyi & Lehner 1971b), can alter results. Changes in the host's CMI due to aging (Gerber & Brown 1974, Weksler & Hiitteroth 1974 can also invalidate findings from groups differing in age.…”
mentioning
confidence: 99%